Production systems Polyware Philippines Incorporated - Ledon, Cecilia M. (College of Engineering, 1985)
Polyware Philippines, Inc. is a manufacturing firm of plastics whose product lines include polybags, polystraps for packing, both hard and soft kinds and polystraps for weaving. In undertaking the study of their present system, the group acquired most of the information and data through interviews with the production manager and with some of the workers in the production department itself. The group came to really understand how their products are produced by closer observations of the production processes. From the interviews, we learned that the latest addition to their product lines, the polystrap for weaving, gives them a monopoly in the local market as well as being entered in the international market. Among the findings of the group is that the factory is a combined feature of both a continuous and job-order production system, that is, the polybags are in job-order production while the rest are in continuous production. In spite of this, their organizational formation is somewhat informal with some responsibilities inherent in a manufacturing firm lumped in what departments they have undertaken or shouldered only by a few personnel. As an example, their purchasing department is supposed to undertake is being accomplished by the personnel in the sales department. The factory also lacks a formalized quality control, but nevertheless, quality control is being practiced both for the raw materials and finished products. A further discussion of how this is carried out was presented by the group. The management also does not use any forecasting method in relation to their products since they believe that any forecasting is useless with the prevailing very irregular price behaviors of raw materials and finished products especially with the present situation our country is in. Another major findings of the group is that they have been incurring costs lately due to maintenance on their machineries. By this we mean that because of the present state their machineries are in, more wastage result from it and several machine hours are being wasted due to repairs, which could have been utilized for further production. This naturally meant a great deal of loss for them. In their inventory, both for raw materials and finished products, a minimum level is being maintained. Again, they have very informal way of determining when to replenish stocks. The basis they have is the current price, in the case of raw materials. If the price seems favorable for them, they procure as much as they can, which they can turn to when prices put them at a disadvantage. In other aspects like procurement, scheduling and production planning, they follow a simple but effective pattern best suited in their present system. After all the acquired informations have been analyzed by the group, it was then clearly shown to us that the main problem of this system is with respect to their maintenance, both in machineries and housekeeping. As mentioned earlier, although definite costs have lately been incurred, they continue to adhere to their policy that have been established since Polyware started its operation. It is with this aspect that the group encountered some difficulties since the management did not keep track of its machine breakdowns and we therefore have no data available to which a model can be formed for calculations which ultimately could have been our basis for the sensitivity analysis. Because of this, the group regrets that no justifiable conclusions can be presented in this study. It is therefore a major recommendation that the management give a closer and more studied attention regarding this matter and the group firmly believes that after this has been accomplished, they, the management, will find a scheme in their maintenance system most profitable for them. It is also the opinion of the group that they not formalize their quality control basing on the factory records and performance with regards to customer feedback they have been known to produce and deliver goods of good quality. In their forecasting system, the group tried to fit a model for them based on the past data they have given to us. We believe that whatever the present economic state is, a certain form of forecasting is most useful, particularly in the continuous production of their products. This would enable the management to make certain plans ahead of time and will assist them in their production planning procedures. While this would be true only for Polyware's production of polystraps, no forecasting method can help them predict how much to produce on the polybags since this is a job-order production. As to the rest of its system components, it is also recommended that they continue with what present procedures they have because such procedures proved effective for their present set-up and have provided them no problems or difficulties both in the past and present to deal with.